ANALISIS SISTEM PENGENDALIAN BIAYA (COST CONTROL FRAMEWORK) PADA PROYEK PELEBARAN JALAN SP.3 LEMPAKE SAMARINDA - SP.3 SAMBERA KALIMANTAN TIMUR - Prana, Edward; Anwar, M.Ruslin; Zaika, Yulvi (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2012)
Edward Prana1, M.Ruslin Anwar2 & Yulvi Zaika31,2 & 3Fakultas Teknik Jurusan Teknik Sipil Universitas Brawijaya MalangAlamat Korespondensi: Jl. MT. Haryono No 167 Malang, Indonesiae-mail: edwarprana@ymail.comABSTRACTIn this study, will be analyzed Cost control framework on one road construction project inEast Kalimantan using Earned Value Concept and Work Break Down Structure. As the object ofstudy is Sp.3 Road Widening Project Lempake (Dublin) - Sp.3 Sambera located in the city ofSamarinda, East Kalimantan. way of acquiring primary data through observation and interviewsdirectly to the project, while secondary data from project documents.Performance costs and time by using Earned Value Concept in terms of the reporting week 25CV and SV value value Positive Negative, indicating that the work has been delayed from the timethe work plan, but the cost is still below the budgeted costs. Resource use efficiency using EarnedValue Fund at week-25 values of 1.11 and SPI CPI of 0.93. Cost performance, while showinggood performance for performance efficiency by less well because of a delay of the planned time.Predicted cost and project completion time estimated the cost for the remaining work on theassumption that the trend of the performance of the project will remain until the end of the project(ETC) amounted to Rp 3, 138,305,144.17 while the estimated cost of up project completion (EAC)is equal to = Rp. 9,871,988,500.07, which means there is no advantage or still under the budget plan(PV) in the amount of Rp. 10,968,876,111.19. While the estimated schedule for the completion ofthe aspects of the job completion time estimates obtained (TE) assuming the performance trend ofthe project remains is 212 days. This means that the project will be delayed approximately 14 daysof 198 days plan.Keywords: Control cost (Cost control framework), Work Break Down Structure, Earned ValueConcept.